Optimizing Accounting Information Systems in the Era of Digital Transformation: Integration of Artificial Intelligence and Blockchain Technology in Increasing Efficiency and Security of Financial Data - Aini, Qurrotul (Maliki Interdisciplinary Journal, 2025)
This essay discusses the integration of Artificial Intelligence (AI) and blockchain technology in Accounting Information Systems (AIS) as a strategic step in optimizing financial data management in the era of digital transformation. AI enables automation of financial recording, analysis, and reporting processes more quickly and accurately, while blockchain provides security and transparency guarantees through a distributed and immutable recording system. The combination of the two improves operational efficiency and reliability of accounting data. However, the implementation of this technology is not free from challenges, such as limited competent human resources, regulatory uncertainty, and potential cybersecurity risks. This essay also discusses several case studies of the application of AI and blockchain in a business environment to illustrate the benefits and obstacles encountered in real terms. Based on this analysis, a number of strategic recommendations are presented, such as strengthening HR training, adjusting regulatory policies, and developing a layered security system to support the implementation of technology comprehensively and sustainably. Thus, it is hoped that digital transformation in the field of accounting can run more effectively, accountably, and adaptively to technological developments in the future.